The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1148/rg.236035085
|View full text |Cite
|
Sign up to set email alerts
|

Multi–Detector Row CT Urography in the Evaluation of Hematuria

Abstract: Hematuria can be well evaluated with a comprehensive contrast material-enhanced multi-detector row computed tomography (CT) protocol that combines unenhanced, nephrographic-phase, and excretory-phase imaging. Unenhanced images are obtained from the kidneys to the bladder and allow optimal detection of renal calculi, a common cause of hematuria. Renal parenchymal abnormalities, particularly masses, are best visualized on nephrographic-phase images, which also provide excellent evaluation of the other abdominal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(52 citation statements)
references
References 30 publications
0
44
0
8
Order By: Relevance
“…Although CT urography is nowadays considered as the most appropriate [25] and the most clinically effective imaging method in the evaluation of patients with hematuria [13,14,26], yield and clinical effectiveness of US should not be disregarded in the evaluation of the urinary bladder. Our experience indicated that US has a good sensitivity and overall accuracy for cystoscopy-proved FBWA even when different but dedicated operators perform sonographic exploration of the bladder.…”
Section: Discussionmentioning
confidence: 99%
“…Although CT urography is nowadays considered as the most appropriate [25] and the most clinically effective imaging method in the evaluation of patients with hematuria [13,14,26], yield and clinical effectiveness of US should not be disregarded in the evaluation of the urinary bladder. Our experience indicated that US has a good sensitivity and overall accuracy for cystoscopy-proved FBWA even when different but dedicated operators perform sonographic exploration of the bladder.…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria were patients younger than 18 years, with indication for non-contrastenhanced abdominal CT scans, or with contraindication for utilization of iodinated contrast agents. Patients whose indication for the scan was investigation of hematuria were also excluded, considering the well established theoretical groundings in literature advocating the need for non-contrastenhanced phase in such cases (11,12) .…”
Section: Methodsmentioning
confidence: 99%
“…MDCT without contrast helps evaluate nephrolithiasis which is one of the main reasons of hematuria and allows imaging from the kidney to the bladder (3).…”
Section: Hematuriamentioning
confidence: 99%
“…Delayed thin slice images from the kidneys to the bladder reveal contrast distended urinary system and are used to detect uroepithelial diseases (3). Pyelographic phase images are obtained 5-15 min after contrast administration and are used to evaluate uroepithelium.…”
Section: Hematuriamentioning
confidence: 99%